Construction and Pathogenicity Analysis of a GFPuv-labeled Peanut Ralstonia solanacearum Strain - Jinling HUANG; Yushuang WU; Huiquan TANG; Minyi HUANG; Ruixue YANG; Qiang WANG; Yong YANG; Xiaodan TAN (Guangdong nongye kexue)
【Objective】The study aimed to construct a GFPuv-labeled peanut Ralstonia solanacearum, which was used to observe the infection pathway in host plants in real-time. Meanwhile, genomic integration sites suitable for exogenous gene were identified.【Method】Through whole-genome analysis of R. solanacearum PeaFJ1 strain, the insertion sites for exogenous gene were selected. The suicide plasmid pK18mobsacB and homologous recombination double exchange technology were employed to integrate the GFPuv gene into the designated site of PeaFJ1 genome. Expression of GFPuv was assessed with fluorescence microscopy under UV light. Growth rate and pathogenicity determination were performed to evaluate the functional activity of the GFPuv-labeled strain.【Result】The GFPuv gene was successfully integrated into the IR3 region of the PeaFJ1 genome, resulting in the construction of stable PeaFJ1-GFPuv strain (that is, GFPuv-labeled strain). Under UV light, the GFPuv-labeled strain exhibited strong green fluorescence, whereas the wild-type PeaFJ1 strain showed no fluorescence. In liquid medium, the OD600 value of PeaFJ1-GFPuv strain exceeded 1.5 after 96 hours; in solid medium, the OD600 value exceeded 0.5 after 48 hours, with colony diameters of 1.0-1.5 mm within three days, showing no significant difference in growth rate compared with that of the wild-type strain. Pathogenicity tests indicated that, the plant wilting mortality rate reached 100% for both PeaFJ1-GFPuv and wild-type PeaFJ1 strains after 11 days of inoculation, with no significant difference. Additionally, measurements of leaf conductivity and bacterial content demonstrated that the proliferation rate of the GFPuv-labeled strain in peanut leaves was comparable to that of the wild-type strain. Fluorescence microscopy observation further verified that the PeaFJ1-GFPuv strain could track its infection pathway in peanut leaves, with the bacteria entering the main leaf veins from the cut site after two days of inoculation and extensively distributed throughout the leaf after nine days of inoculation.【Conclusion】The PeaFJ1-GFPuv strain integrated into the IR3 region of GFPuv was successfully constructed. There was no significant difference in biological characteristics and pathogenicity between the GFPuv-labeled strain and the wild-type PeaFJ1, indicating that the IR3 region was an effective site for gene complementation. The GFPuv-labeled strain showed strong green fluorescence under UV light, which could be used to observe the infection pathway of R. solanacearum.